(untitled) (e-Journal of Linguistics, 2024)
The aims of this research are to (1) To find out the types of conversational implicatures (2) to describe how the implicature exist (to find out the types of non-observance maxim of cooperative principle) and (3) To find the purpose of generate implicature. This research was descriptive qualitative. The data of this research were the dialog in BBC News Indonesia’s Interview with Joko Widodo. The researcher obtained the data by note-taking technique. First, the researcher watched the video interview and make the transcript from the dialogues. Then, the researcher re-read the transcribed dialogues and classified the data according to theory of implicature and non-observance maxim of cooperative principle by Grice. In the data analysis the researcher applied qualitative data method by Miles and Huberman (2014). The results of the research found there were 16 particular implicatures identified out of 18 of data in the dialogue, while the other 2 were general implicatures. Additionally, the researcher identified a lot of disregarded maxim forms. The most frequently disregarded maxim was the flouting of the maxim of quantity. Based on the research findings, it was observed that Joko Widodo often commits violations of the maxim of quantity in order to provide additional information or to strengthen his arguments.